Evaluasi Kinerja Keuangan Pada PT. Bunas Finance Indonesia (BFI) Tbk - -, Ida Noorpanti (EKONOMIA, 2015)
PT. Bunas Finance Indonesia is one of the auto finance company. The purpose of this study is to evaluate the financial performance. PT. Bunas Finance Indonesia Tbk from years 2011 - 2012 in terms of profitability, liquidity, and solvency. Formulation of the problem raised is